Functions of METTL1/WDR4 and QKI as m7G modification - related enzymes in digestive diseases - Zhou, Wenyan; Yi, Yan; Cao, Wenyu; Zhong, Xiaolin; Chen, Ling (Frontiers in Pharmacology, 2025)
N7-methylguanosine (m7G) modification is one of the most prevalent forms of chemical modification in RNA molecules, which plays an important role in biological processes such as RNA stability, translation regulation and ribosome recognition. Methyl-transferation of m7G modification is catalyzed by the enzyme complex of methyltransferase-like 1 (METTL1) and WD repeat domain 4 (WDR4), and Quaking (QKI) recognizes internal m7G methylated mRNA and regulates mRNA translation and stabilization. Recent studies have found that m7G modification - related enzymes are associated with the onset and progression of digestive cancer, such as colorectal cancer, liver cancer, and other digestive diseases such as ulcerative colitis. This review will focus on the latest research progress on the roles of m7G methyltransferase METTL1/WDR4 and recognized enzyme QKI in digestive diseases.